PENGARUH KUALITAS PELAYANAN, KEWAJIBAN MORAL, DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK HOTEL DI KOTA TEGAL - Desthi Dwi Agita; Asrofi Langgeng Noermansyah (Monex: Journal of Accounting Research, 2020)
This study aims to determine the effect of service quality, moral obligations, and tax penalties on hotel taxpayer compliance in Tegal City. The data collection method uses the questionnaire, observation, interview, and literature study methods. The population in this study were all hotel taxpayers registered with Badan Keuangan Daerah Kota Tegal as many as 94 taxpayers. The sampling method uses a purposive sampling technique so that the samples used are 75 hotel taxpayers based on the number of taxpayers who are compliant in paying hotel taxes. The method of data analysis uses multiple linear regression analysis. The results showed that the variable service quality did not affect the compliance of hotel taxpayers in Tegal City. Meanwhile, moral obligations and tax penalties have a positive effect on hotel taxpayer compliance in Tegal City